Consumer’s Perception about Use of Recycled Water for Urban Agriculture - Aman Preet Singh Brar,; Bairam Oogra, (Journal of Agricultural Extension Management, 2025)
Urban agriculture could provide a complementary strategy to reduce urban poverty, food insecurity and enhance urban environmental management. Use of typical urban resources could include labour, organic waste and urban waste water for irrigation. However before implementing such a project, the view point of consumers needs to be considered. This study carried out in urban Punjab attempts to understand consumers' perception about use of waste water for promoting urban agriculture. The study reveals that over 80 per. cent of the respondents in urban areas are willing to use recycled water provided quality of treated water is assured. In addition, proper education of the consumers and transparency about quality of waste water will lead to sure success of the project